Integrating the online OurRelationship program into a stepped‐care model of couple therapy. Issue 2 (18th December 2020) - Le, Yunying; Rothman, Karen; Christensen, Andrew; Doss, Brian D.
Abstract : Due to various barriers, most relationally distressed couples do not seek couple therapy. With the COVID‐19 pandemic, many of these barriers are further exacerbated, while the need for relationship services has increased. To increase the reach of couple therapy both during and after the pandemic, we propose a stepped‐care model that utilises technology as a precursor to couple therapy and acts as an integral component of it. In this paper, we first introduce the OurRelationship program – an evidence‐based online relationship program that improves both relationship and individual functioning in several large‐scale, nationwide trials. We then describe how therapists can incorporate this program into an abbreviated, eight‐session course of couple therapy. We expect this integration will be useful to couple therapists from a variety of theoretical orientations and will address numerous common barriers to treatment including cost, scheduling difficulties and geographic distance from the therapist. Practitioner points: Couple therapists can leverage technology to increase their reach both during and after the COVID‐19 pandemic. The online OurRelationship program improves relationship and individual functioning in several nationwide clinical trials. The OurRelationship program can be integrated into an eight‐session course of couple therapy to serve couples who would otherwise be unable or unwilling to attend therapy. Abstract : 将 "我们的关系" 线上项目整合到分步关怀模式的夫妻治疗中: 由于各种各样的障碍，大多数关系痛苦的夫妇并不寻求夫妻治疗。随着新型冠状病毒的流行，许多这些障碍进一步加剧，同时对关系服务的需求也增加了。为了在大流行期间和之后增加夫妻治疗所触及的范围，我们提出了一种分步关怀模式，该模式利用科技作为夫妻治疗的引入，同时作为其组成部分。在本文中，我们首先介绍了"我们的关系"项目，这是一个实证的线上关系项目，它在几个大规模的全国性试验中改善了人际关系和个人功能。然后，我们描述治疗师如何能将这个项目融入一个简短的八次会面的夫妻治疗中。我们期望这种整合将有助于不同理论方向的夫妻治疗师，并解决许多常见的治疗障碍，包括成本、日程安排困难和与治疗师的地理距离等。 对从业者的启示: 在新冠病毒大流行期间和之后，夫妻治疗师可以利用科技来增加他们的治疗范围。 "我们的关系"线上项目在多个全国性临床试验中改善了人际关系和个人功能。 "我们的关系"项目可以整合到一个八次的夫妻治疗中，为那些在其他情况下无法或不愿参加治疗的夫妇提供服务。 Abstract : Integración del programa online OurRelationship (Nuestra relacion) en un modelo de atención escalonada de terapia de pareja: Debido a dificultades diversas, la mayoría de las parejas con problemas relacionales no buscan terapia de pareja. Con la pandemia del COVID‐19, muchas de estas dificultades se exacerban aún más, mientras que la necesidad de servicios de ayuda relacional ha aumentado. Para aumentar el alcance de la terapia de pareja durante y después de la pandemia, proponemos un modelo de atención escalonada que utiliza la tecnología como precursora de la terapia de pareja y actúa como un componente integral de la misma. En este artículo, primero presentamos el programa OurRelationship, un programa online basado en evidencia que ha demostrado mejorar tanto la relación de pareja como el funcionamiento individual en varios ensayos a gran escala a nivel nacional. Luego describimos cómo los terapeutas pueden incorporar este programa en un modelo abreviado de ocho sesiones de terapia de pareja. Esperamos que esta integración sea útil para terapeutas de pareja con diversas orientaciones teóricas y que sirva para abordar numerosas barreras comunes al tratamiento, incluido el costo, las dificultades de agenda y la distancia geográfica del terapeuta. Puntos de implicación práctica: Los terapeutas de pareja pueden aprovechar la tecnología para aumentar su alcance tanto durante como después de la pandemia del COVID‐19. El programa online OurRelationship ha demostrado en varios ensayos clínicos a nivel nacional que mejora las relaciones y el funcionamiento individual. El programa OurRelationship se puede integrar en de ocho sesiones de terapia de pareja para atender a parejas que de otra manera no pueden o no quieren asistir a terapia.